Strategic risk management: the case of HBOS - McConnell, Patrick (Henry Stewart Talks, 2017)
History of the Halifax/Bank of Scotland, The collapse of HBOS, The flawed strategy, Lessons from HBOS, What is strategy, What is strategic risk, Management of strategic risks